Analysis of the Effect of Quality Management System Implementation on Service Quality - Aritonang, Barita (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Improving the quality of services in the health sector, especially in hospitals, has become one of the main concerns in various countries, including Indonesia. Quality health services are essential in creating patient satisfaction and improving the effectiveness of the health care system as a whole. Objective: This study aims to determine the extent of the relationship and influence between the variables of quality management system implementation on service quality at RSUD Dr. Pirngadi Medan City. Methods: This research is a quantitative study with an associative approach, associative research is used to test the cause-and-effect relationship between two or more variables through statistical analysis. The sample amounted to 86 respondents. Data were collected using a structured questionnaire and the outcome report was analyzed with the chi-square test at a significance level of p<0.05. Research Results: the implementation of the quality management system has a positive and significant effect on service quality at RSUD Dr. Pirngadi Medan City. The hospital needs to continue to improve the implementation of the quality management system consistently, especially in the aspects of HR training and the implementation of continuous quality audits, in order to improve the quality of services received by patients. Conclusion: hospitals need to pay attention to improving physical facilities, such as the cleanliness of treatment rooms and the provision of more modern medical equipment. With these improvements, hospitals can improve the tangible dimension of service quality, which in turn will increase overall patient satisfaction.